Analisis Kinerja Keuangan KSP Kopdit Swasti Sari Berbasis Metode PEARLS - Maria Viviana Nurak Lewar; Siktania Maria Diliana; Magdalena Nona Ice (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to determine the results of financial performance analysis using the PEARLS (Protection, Effective Financial Structure, Asset Quality, Rates of Return and Costs, Liquidity, and Signs of Growth) method at KSP Kopdit Swasti Sari for the 2017-2021 period. The method used in this study is quantitative descriptive research. The variables used in this study are the financial performance of Credit Cooperatives based on the PEARLS method using 13 ratios according to the ACCU (Association of Asian Confederation of Credit Unions), and the data sources used are primary and secondary data. The results of the study show that the financial performance of KSP Kopdit Swasti Sari using 13 ratios from the PEARLS method shows that the performance is still unhealthy, because of these 13 ratios, many ratios are still in the bad and medium categories.